Attitudes towards Chagas' disease in an endemic Brazilian community Crenças populares relativas à doença de Chagas em uma comunidade de área endêmica do Brasil - Sarah Williams-Blangero; John L. VandeBerg; Antonio R. L. Teixeira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1999)
Chagas' disease remains a major public health concern throughout much of Latin America. In Brazil, segments of the population experience Trypanosoma cruzi infection rates as high as 65%, indicating that control programs are still needed. Few data are available concerning people's health beliefs related to Chagas' disease in heavily infected populations. Such health beliefs may significantly impact the effectiveness of intervention schemes. The purpose of this study was to assess health beliefs related to Chagas' disease in a population experiencing high infection rates with the causal parasite. The focal population for the study consisted of the residents of Posse, a rural community in the State of Goiás. The results indicate that a majority of the population had a high degree of knowledge about Chagas' disease and the vector involved in its transmission. These findings indicate that control programs conducted by the Brazilian Ministry of Health have included effective educational components. A doença de Chagas persiste como importante problema de saúde pública em grande parte da América Latina. No Brasil, vários segmentos da população apresentam taxas de infecção pelo Trypanosoma cruzi que chegam até 65%, sugerindo que os programas de controle ainda são necessários. Há poucos dados disponíveis sobre as crenças populares relativas à doença de Chagas entre comunidades com altas taxas de infecção. Tais crenças podem ter um impacto significativo sobre a eficácia das intervenções. O objetivo deste estudo é avaliar as crenças relativas à doença de Chagas numa população com altas taxas de infecção pelo agente etiológico da doença. A população-alvo do estudo foi composta de moradores da Posse, uma comunidade rural no Estado de Goiás. Os resultados indicam que a maioria da população tinha um alto grau de conhecimento quanto à doença de Chagas e seu vetor. Os achados apontam para a eficácia dos componentes educativos dos programas de controle implementados pelo Ministério da Saúde.